Antioxidants in Age-Related Macular Degeneration: Lights and Shadows - Uday Pratap Singh Parmar; Pier Luigi Surico; Tommaso Mori; Rohan Bir Singh; Francesco Cutrupi; Pramila Premkishore; Gabriele Gallo Afflitto; Antonio Di Zazzo; Marco Coassin; Francesco Romano (Antioxidants)
Age-related macular degeneration (AMD) is a leading cause of vision impairment worldwide, primarily driven by oxidative stress and inflammation. This review examines the role of antioxidants in mitigating oxidative damage, emphasizing both their therapeutic potential and limitations in AMD management. Key findings underscore the efficacy of specific antioxidants, including vitamins C and E, lutein, zeaxanthin, and Coenzyme Q10, in slowing AMD progression. Landmark studies such as AREDS and AREDS2 have shaped current antioxidant formulations, although challenges persist, including patient variability and long-term safety concerns. Emerging therapies, such as mitochondrial-targeted antioxidants and novel compounds like saffron and resveratrol, offer promising avenues for AMD treatment. Complementary lifestyle interventions, including antioxidant-rich diets and physical activity, further support holistic management approaches. This review highlights the critical role of antioxidants in AMD therapy, advocating for personalized strategies to optimize patient outcomes.